Addressing the needs of colorectal cancer survivors: current strategies and future directions. Issue 6 (June 2015) - Wong, Evelyn Yi Ting; Chua, Clarinda; Beh, Sok Yuen; Koh, Dennis; Chong, Dawn; Tan, Iain Beehuat
<x xml:space="preserve">Abstract</x> Colorectal cancer (CRC) is one of the three topmost common cancers in men and the second most common cancer in women worldwide. With current advances in the medical and surgical treatment of CRC, care has slowly transformed to curative treatment. With these advances, CRC survivors are increasing in numbers and these patients have a unique range of medical, physical and psychological needs that require regular follow-up. In 2006, the Institute of Medicine recommended that cancer survivors who are completing primary treatment receive a survivorship care plan. There are many different programs of different complexity that are implemented for CRC survivors. This review outlines the needs of CRC survivors, the current surveillance techniques used in the continuing care of patients with CRC after curative treatment and the evidence behind these strategies.